PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Majid Abdullah; Endro Sukotjo; Eliyanti Agus Mokodompit (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to determine the simultaneous and partial effects of variable brand image, price and product quality on purchasing decisions at Brownte Kendari Shop.This study uses a quantitative approach and is categorized as survey research, where the research instrument is a questionnaire. The object of this study is customers who buy Brownte products. The population in this study were all customers who bought unknown amount of Brownte products. The sample in this study was 80 respondents. The sampling technique used in this study was to use accidental sampling, the method of collecting data in this study was using questionnaires and interviews. This study uses multiple linear regression analysis with the SPSS 16.0 program.  The results of this study use that Brand Image, Price and Product Quality Have Positive and Significant Effects on Purchase Decisions.Keywords: brand image, price, product quality, purchasing decision